Yaxley's Cat - Robert Westall (Scholastics Inc USA, 1993)
When Tim, Jane, and their mother rent Mrs. Yaxley's old cottage, they never expect to discover that old Yaxley was the victim of a supernatural evil that may still lurk in his home. Reprint.
Keywords: Mystery -- Mystery